2021
DOI: 10.3390/ai2010006
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning and Feature Selection for Alfalfa Yield Prediction

Abstract: Predicting alfalfa biomass and crop yield for livestock feed is important to the daily lives of virtually everyone, and many features of data from this domain combined with corresponding weather data can be used to train machine learning models for yield prediction. In this work, we used yield data of different alfalfa varieties from multiple years in Kentucky and Georgia, and we compared the impact of different feature selection methods on machine learning (ML) models trained to predict alfalfa yield. Linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
(31 reference statements)
2
22
0
Order By: Relevance
“…The results showed that the correlation-based method is better than others. With feature selection, the k -nearest neighbor and random forest methods could predict alfalfa yield [ 29 ]. In this study, we used five methods to predict FD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the correlation-based method is better than others. With feature selection, the k -nearest neighbor and random forest methods could predict alfalfa yield [ 29 ]. In this study, we used five methods to predict FD.…”
Section: Discussionmentioning
confidence: 99%
“…In alfalfa yield, machine learning models can use weather, historical yield, and sown date to make predictions. Published results have shown that the k -nearest neighbor and random forest methods performed well [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using this vector, it is possible to discriminate one class of objects from another. The final step is classification [32]. Note that the choice of a suitable classifier depends on the specific problem.…”
Section: Application Of Machine Learning and Image Processing In Disease Identificationmentioning
confidence: 99%
“…In article [ 8 ], the input data of soil and crop properties were used to predict yield. ML algorithms can be used to predict alfalfa yield [ 9 ], maize yield and nitrate loss [ 10 ], and to assess the seasonal nitrogen status in maize [ 11 , 12 ], carrot yield mapping [ 13 ], soil suitability for growing individual crops [ 14 ] and peach tree nutrients at the local level [ 15 ].…”
Section: State-of-the-artmentioning
confidence: 99%